2018
DOI: 10.1016/j.jtrangeo.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The evolving structure of the Southeast Asian air transport network through the lens of complex networks, 1979–2012

Abstract: A B S T R A C TThis paper presents a novel approach to investigating and understanding the evolving structure of the Southeast Asian air transport network (SAAN) over the period 1979-2012. Our approach captures the main topological and spatial changes from a complex network perspective. We find that the SAAN combines a relatively stable topological structure with a changing multilayered geographical structure. Statistical analysis indicates that the SAAN is a scale-free network with an increasing number of hub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 66 publications
0
50
0
3
Order By: Relevance
“…To explore the dynamics of China's railway network, this paper applied the commonly used complex network indices [22,24,[37][38][39]. However, some cities had a different number of train stations at different points during the four stages covered by this study.…”
Section: Network Indicesmentioning
confidence: 99%
“…To explore the dynamics of China's railway network, this paper applied the commonly used complex network indices [22,24,[37][38][39]. However, some cities had a different number of train stations at different points during the four stages covered by this study.…”
Section: Network Indicesmentioning
confidence: 99%
“…This phenomenon is clearly observed in Community 3, Community 4, and Community 6. Considering that there is a strong correlation between the freight linkages and the distribution features of the goods, this view is verified through analysis [24]. Therefore, a reliable or possible explanation for this phenomenon is the spatial distribution features of the goods.…”
Section: Clustering Characteristics Of the Freight Networkmentioning
confidence: 65%
“…A large number of studies have identified the characteristics of transportation networks based on massive amounts of travel data, including air passenger flow, rail passenger flow, traffic flow, and big geospatial data. Wang et al [22], Lao et al [23], and Dai et al [24] explored the spatial structure of an air transportation network using aviation passenger data. Zhong et al [25] examined the hierarchical structure of the China passenger railway transportation network and conducted a comparison analysis of the air transportation network and the railway transportation network.…”
Section: Introductionmentioning
confidence: 99%
“…Under the process of globalization, economic activities are becoming more frequent worldwide, creating a new economic and social landscape in the global space [7]. In the study of the world city network, much research has been carried out on three important aspects: transportation networks [8][9][10][11][12], social and cultural networks [13][14][15], and business cooperation networks [9,16,17]. ese studies have deepened our understanding of the interrelationships between cities and provide a reference for studying UA networks in smaller regions.…”
Section: Introductionmentioning
confidence: 99%